"Gruppo di tenda per esterni collegato alla parte posteriore di una scocca di autoveicolo" - SORLINI, Maddalena; BRUNETTI, Luca; RANDAZZO, Cristina (2024)
A motor-vehicle comprises an outdoor tent assembly (1 ) connected to the rear part of the body (S) and defining a closed and sheltered environment provided for housing one or more subjects. In the assembled configuration of the tent group (1 ), the tailgate (20) of the vehicle is in the raised open position and said closed and sheltered environment extends behind the motor-vehicle body (S). The tailgate (20) comprises an integrated extension system (22), comprising at least one support and extension element (23) maneuverable between a retracted position and an extended position suitable for defining an extension of the tailgate (20). In the assembled configuration of the tent assembly (1 ), the support and extension element (23) is in its extended position and the upper wall (2) of the tent assembly (1 ) extends above and along the tailgate (20) and along the support element (23).